2005
DOI: 10.1007/s00167-004-0615-4
|View full text |Cite
|
Sign up to set email alerts
|

Open Bankart repair with suture anchors for traumatic recurrent anterior shoulder instability: comparison of results between small and large Bankart lesions

Abstract: This retrospective study was to demonstrate the clinical outcome of open Bankart repair with suture anchors for recurrent anterior shoulder instability, and to compare surgical results of small (<3 clock units) and large (>3 clock units) Bankart lesions. With an average follow‐up of 55.6 months (2–8 years), there were 82 patients (60 right, 22 left shoulders) with the mean age of 27 years accepting open Bankart repair with suture anchors and capsular shift procedure by the same team. According to surgical find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…All 96 articles were individually reviewed by 2 reviewers, resulting in 29 articles that met the inclusion criteria and were included in this report ( Figure 1 ). 2 – 5 , 7 20 , 22 33 …”
Section: Resultsmentioning
confidence: 99%
“…All 96 articles were individually reviewed by 2 reviewers, resulting in 29 articles that met the inclusion criteria and were included in this report ( Figure 1 ). 2 – 5 , 7 20 , 22 33 …”
Section: Resultsmentioning
confidence: 99%
“…29 Open Bankart repair with suture anchors associated with the capsular shift procedure was more effective in small Bankart lesions compared to large ones. 30 Kamath et al 31 reported that two double-loaded suture anchors were better or equal to three single-loaded suture anchors because it needed fewer anchor holes in the glenoid bone, thus decreasing the incidence of postsurgical glenoid fracture. In patients who underwent an arthroscopic bony Bankart bridge to treat a Bankart lesion, there was an average glenoid bone loss of 29% ( n = 14): Millett et al 32 observed that successful joint stability was achieved in 93%.…”
Section: Discussionmentioning
confidence: 99%
“…29 Open Bankart repair with suture anchors associated with the capsular shift procedure was more effective in small Bankart lesions compared to large ones. 30 Kamath et al 31 reported that two double-loaded suture anchors were better or equal to three single-loaded suture anchors because it needed fewer anchor holes in the glenoid bone, thus decreasing the incidence of postsurgical glenoid fracture.…”
Section: Discussionmentioning
confidence: 99%
“…8,17,18,20 This indicates the need for anatomic bone reconstruction in cases of large defects of the anterior glenoid rim. Lai et al 16 and Rhee and Lim 24 found that Bankart lesion size is an important factor in surgical outcome after Bankart repair with simple capsular reattachment. Regardless of this technique being arthroscopic or open, they concluded that poor surgical outcomes would follow from large bony Bankart lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The defects are associated with poor arthroscopic stabilization outcome without bone graft for significant bony loss of the anterior glenoid. 4,6,16,26,31…”
mentioning
confidence: 99%